The Search for Synergy: Interrelating Medical Work and Patient Care Information Systems - Berg, M. (Methods of Information in Medicine, 2003)
Objectives: This article aims to search for the way patient care information systems can be most fruitfully put to work in health care.Methods: Given the calls for improved health care quality, there is a need for IT’s coordination capacities in health care. Yet IT’s track record in this area is less than many expected. Moreover, many argue that the nature of health care work sets natural limits to the possibilities of IT to revolutionize this work. Starting with an analysis of the paper record, this article explores the way IT and professional work can be interrelated synergistically.Results: Two principles are discussed: 1) The key to a fruitful operation of IT in health care work lies in the unraveling of the care process, and the redistribution of tasks between professionals and the IT application. 2) Professionals should be given the skills and resources to adapt the IT application’s demands to the needs of their work practices.Conclusion: IT can bring true process support to health care when taking the two principles discussed here into account.
Keywords: Patient care information systems (PCIS); health care work; electronic patient records; benefits of PCIS; implementation of information systems; sociotechnical approaches